A Study of Student Teachers` Literacy and Challenges in Using Technology for English Language Teaching - Ahmad Syauqi Harsyah; Dedy Kurniawan; Lilik Ulfiati (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2022)
Technology has played an important role in human life including education. Teachers in this century are required to have technology skills for language teaching. However, in order to understand their level of literacy and challenges faced in implementing technology a study is required. The present study investigated student teacher`s literacy and challenges in using technology. This research was conducted by using mix method with sequential explanatory design. Sixty-one students of the seventh semester of English study program Universitas Jambi were selected as the participant in this research. In the quantitative phase Researchers used survey to collect the data to measure their experience, views, and literacy on technology using a likert scale of one to five. In the qualitative phase, the data were collected using interview towards eighth students are selected purposively from the high score and low score and analyze it by using content analysis. The survey showed that the participating student teachers have: 1) adequate experiences in using technology(x=3.66), 2). Positive views on technology(x=3.56), 3).average literacy on technology(x=3.87). The results of the interview showed some challenges faced by student teachers in implementing technology, The lack of facilities is the biggest challenge. The implication of the research is also discussed